2010
DOI: 10.1016/j.physleta.2009.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis and design of amplitude death induced by a time-varying delay connection

Abstract: The present paper considers amplitude death in a pair of oscillators coupled by a time-varying delay connection. A linear stability analysis is used to derive the boundary curves for amplitude death in a connection parameters space. The delay time can be arbitrarily long for certain amplitude of delay variation and coupling strength. A simple systematic procedure for designing such variation and strength is provided. The theoretical results are verified by a numerical simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
(24 reference statements)
0
34
0
Order By: Relevance
“…One application is to the stabilization of fixed points [60,61,62]. Velocity delayed coupling has been also explored in the context of amplitude death [63,64] (see Sec.…”
Section: Delay Interactionmentioning
confidence: 99%
“…One application is to the stabilization of fixed points [60,61,62]. Velocity delayed coupling has been also explored in the context of amplitude death [63,64] (see Sec.…”
Section: Delay Interactionmentioning
confidence: 99%
“…The essence of the improved control mechanism lies in the delay distribution, which is created by the modulation. It has already been reported that delay distributions in coupled oscillators lead to stabilization of steady states [8][9][10]. The same mechanism applies to self-feedback on a single oscillator.…”
Section: Introductionmentioning
confidence: 70%
“…When the amplitude δ is increased, the AD region in parameter space increases correspondingly. Konishi et al [25] derive the analytic conditions for AD for arbitrary time-delay values in the above system to obtain the result that when δ = π/ω where ω << Ω and µ < ω(2 + π)/4π, the AD region becomes unbounded. Thus the use of time-dependent delay provides a systematic procedure for designing AD by tuning appropriate system parameters.…”
Section: Scenariosmentioning
confidence: 99%